Effect of natural fish tail palm fiber on the workability and mechanical properties of fiber reinforced concrete - Ramalingam Vijayalakshmi; Ramesh Keerthika; Arumugam Modhagapriyan; Muralidharan Vaishnavi (Građevinski Materijali i Konstrukcije, 2022)
To improve the pre-cracking behavior and post peak strength of concrete composites, a new variety of natural fiber called Fish Tail Palm Fibers was used as micro reinforcement in concrete. Fish Tail Palm Fibers (FTPF) are completely renewable natural resources and are available in abundance, in many parts of the country including India. Three different volume fractions, (0.1%, 0.2% and 0.3%, and three different lengths of fibers (10 mm, 20 mm and 30 mm) were chosen as the parameters for investigation. Silane treated FTPF was added to concrete and the fresh and mechanical properties were studied. The slump values were slightly affected by the increase in volume fraction of fibers, as the viscosity of concrete increases with fiber content. The compressive strength of the control specimen was 30 MPa (M30). The maximum compressive strength, splitting tensile strength, and flexural strength of Fish Tail Palm Fiber Reinforced Concrete (FTPFRC) specimens are 36 MPa, 2.82 MPa and 4.2 MPa respectively, which were recorded for specimens with 0.2 Volume Fraction (VF) and 30 mm Fiber Length (FL). The increase in the compressive strength, splitting tensile strength and flexure strength is about 20 %, 22% and 30 % with the addition of 0.2 VF of fibers. The findings indicate that the incorporation of fish tail palm fibers reduced the work-ability of concrete. But the mechanical characteristics such as compressive strength, splitting tensile strength, flexural strength, and impact resistance were enhanced with the increase in fiber content and fiber length.